Study of Severe Acute Maternal Morbidity (SAMM) in A Tertiary Care Hospital (Journal of Shaheed Suhrawardy Medical College, 2018)
Background : Severe maternal morbidity also known as ‘near miss’ may be a good indicator of the quality and effectiveness of obstetric care, as it may identify priorities in maternal care more rapidly than mortality alone.Objective : The objectives of this study was to observe the pattern of severe acute maternal morbidity (SAMM) and its associated factors in a tertiary care hospital.Study design and setting : This descriptive cross-sectional study was done from August 2011 to February 2012 at Dhaka Medical College Hospital (DMCH), which is a tertiary care hospital in Dhaka city.Methods : A total 100 consecutive cases of SAMM were taken from Obstetrics and Gynaecology department of DMCH. Five factor scoring system was used to identify the SAMM cases from all the severe obstetric morbidity. For each case of SAMM, data was collected on a) Nature of obstetric complication(s) b) Units of blood transfusion c) Presence of organ-system dysfunction/ failure d) ICU admission e) Length of hospital stay.Results : In this study severe acute maternal morbidities occur in a prevalence of 2.68% and ratio of maternal death was 6.43 per 1000 deliveries. The most frequent primary obstetric factors of severe morbidity detected in this sample were post partum hemorrhage (29%), eclampsia (24%) and sepsis (16%). Other causes were ectopic pregnancy (8%), obstructed labour (7%), ante-partum hemorrhage (5%), abortion (4%), ruptured uterus (3%), anesthetic complication (2%) and miss matched blood transfusion (2%).Conclusion : This study suggests that the treatment of SAMM cases may be improved by developing evidence-based protocols for the management of hemorrhage, eclampsia and infection.J Shaheed Suhrawardy Med Coll, December 2016, Vol.8(2); 58-62